2016
DOI: 10.1371/journal.pone.0165144
|View full text |Cite
|
Sign up to set email alerts
|

Behavioural Phenotyping of APPswe/PS1δE9 Mice: Age-Rrelated Changes and Effect of Long-Term Paroxetine Treatment

Abstract: Alzheimer’s disease (AD) is a devastating illness characterized by a progressive loss of cognitive, social, and emotional functions, including memory impairments and more global cognitive deficits. Clinical-epidemiological evidence suggests that neuropsychiatric symptoms precede the onset of cognitive symptoms both in humans with early and late onset AD. The behavioural profile promoted by the AD pathology is believed to associate with degeneration of the serotonergic system. Using the APPswe/PS1δE9 model of A… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

9
22
2

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 36 publications
(35 citation statements)
references
References 51 publications
9
22
2
Order By: Relevance
“…We observed age effect on general locomotion and exploration of novel environment for the WT and APP/PS1 mice (Fig. 2), which is consistent with previous findings showing reduced locomotion with age in mice [38]. However, treatment effect on locomotion and exploration was significant only for the APP/PS1‐rhu‐EPO mice, and rhu‐EPO significantly reduced locomotion and exploration compared to WT‐saline mice.…”
Section: Discussionsupporting
confidence: 90%
“…We observed age effect on general locomotion and exploration of novel environment for the WT and APP/PS1 mice (Fig. 2), which is consistent with previous findings showing reduced locomotion with age in mice [38]. However, treatment effect on locomotion and exploration was significant only for the APP/PS1‐rhu‐EPO mice, and rhu‐EPO significantly reduced locomotion and exploration compared to WT‐saline mice.…”
Section: Discussionsupporting
confidence: 90%
“…We observed no changes in the levels of Aβ40 or Aβ42 in the hippocampus of escitalopram-treated compared with vehicle-treated mice. Our observations differ from recent clinical and in vivo studies in which researchers have reported Aβ-reducing effects of chronic and acute antidepressant treatment [ 24 , 25 , 32 , 33 , 40 ], although others have also been unable to detect such Aβ-reducing effects [ 38 , 41 ]. Human subjects with a history of antidepressant drug treatment showed reduced cortical amyloid load compared with non-treated subjects, estimated by positron emission computed tomographic imaging using the amyloid-binding [ 11 C]-Pittsburgh compound B (PIB) radioligand [ 24 ].…”
Section: Discussioncontrasting
confidence: 99%
“…for 28 days has furthermore been shown to completely inhibit the growth of plaques without affecting their elimination [ 32 ]. Results at our own laboratory have suggested, however, that 9-month treatment with paroxetine (30 mg/kg/day being reduced to 10 mg/kg/day and ultimately 5 mg/kg/day) per os has no effect on plaque load in the neocortex of 18-month-old APP/PS1 mice [ 41 ], although a significant effect was observed in the hippocampus of the same mice [ 40 ]. Although these findings suggest that a high dosage of paroxetine may have an effect on plaque load at least in the hippocampus, they at the same time emphasise that paroxetine treatment by no means ameliorates plaque load when administered to aging mice in which the amyloid plaques are well-developed.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies on the behaviors of APPswe/PS1dE9 mice mainly focus on the aspects of cognitive dysfunction. Only limited literature is available on the non-cognitive abnormalities of these AD model mice (Pietropaolo et al, 2012; Bilkei-Gorzo et al, 2014; Janus et al, 2015; Verma et al, 2015; Olesen et al, 2016). For example, Filali and colleagues (2011) reported that 6-month-old APPswe/PS1dE9 mice exhibit reduced social interaction and hyperactivity.…”
Section: Discussionmentioning
confidence: 99%
“…APPswe/PS1dE9 mice that over express the Swedish mutation of amyloid precursor protein (APP) together with presenilin1 (PS1) deleted in exon 9 display progressive age-related increases in brain parenchymal beta-amyloid β (Aβ) load and cognitive dysfunction (Trinchese et al, 2004; Reiserer et al, 2007). This AD mouse model also exhibits non-cognitive behavioral abnormalities, including anxiety, hyperactivity, and social behavior deficits (Pietropaolo et al, 2012; Bilkei-Gorzo, 2014; Janus et al, 2015; Olesen et al, 2016). However, there is no systematic analysis of mental behaviors in APP/PS1 mice before the onset of cognitive impairment, warranting investigation into the exact pathophysiology.…”
Section: Introductionmentioning
confidence: 99%